2014
DOI: 10.7314/apjcp.2014.15.2.501
|View full text |Cite
|
Sign up to set email alerts
|

An Update on Occupation and Prostate Cancer

Abstract: Background: Our aim was to identify gaps and limitations in the current literature and to make recommendations for future research required to address these. Materials and Methods: We reviewed occupational exposures and related factors associated with the risk of prostate cancer between 2000 and 2012. These included chemical, ergonomic, physical or environmental, and psychosocial factors which have been reported by epidemiological studies across a range of industries. Results: The results are inconsistent from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 103 publications
0
26
1
2
Order By: Relevance
“…A high risk of developing lung cancer and other respiratory diseases across workers and residents living in high buildings located in Pratunam area, Thailand (Pongpiachan et al, 2013c). In addition, except lung cancer, PAHs were also implicated in prostate cancer risk and gastric cancer (Doolan et al, 2014;Behnampour et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…A high risk of developing lung cancer and other respiratory diseases across workers and residents living in high buildings located in Pratunam area, Thailand (Pongpiachan et al, 2013c). In addition, except lung cancer, PAHs were also implicated in prostate cancer risk and gastric cancer (Doolan et al, 2014;Behnampour et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…More recent systematic review studies or case-control studies reported positive association between exposure to pesticides and several cancers including prostate cancer (Van Maele-Fabry and Willems, 2004;Koutros et al, 2010;Doolan G et al, 2014), non-Hodgkin lymphoma (NHL) (Merhi et al, 2007;Balasubramaniam et al, 2013;Yildirim et al, 2013;Schinasi and Leon, 2014), leukemia (Merhi et al, 2007;Van Maele-Fabry et al, 2008), multiple myeloma (Merhi et al, 2007) and lung cancer (Ganesh et al, 2011;Luqman et al, 2014). In the case of esophageal or gastric cancer, no relationship with pesticide usage was reported in recent Turkey study (Yildirim et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Identification of mechanisms affecting malignancy of prostate etiology and development results in designing potent treatments. Since it is a multi-factorial disease induced by genetic (Yang et al, 2013) and environmental factors, there are numerous factors which are known to cause or increase the incidence of PCa (Doolan et al, 2014). A proven association between prevalence and mortality rate of prostate cancer and smoking has led many to consider smoking as a significant exogenous risk factor for PCa progress (Huncharek et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is recognized as the second leading cause of cancer death in males (Heidenreich et al, 2013). A few risk factors for developing PCa are currently well-known (Doolan et al, 2014). It has been shown that this common malignancy probably originates from a combination of factors including advanced age, ethnicity, family history, endogenous hormones and specific diseases (Quinn and Babb, 2002;Crawford, 2003).…”
Section: Introductionmentioning
confidence: 99%